2017
DOI: 10.1155/2017/5716296
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bearing Fault Detection Using Step-Varying Vibrational Resonance Based on Duffing Oscillator Nonlinear System

Abstract: Bearing is a key part of rotary machines, and its working condition is critical in normal operation of rotary machines. Vibrational signals are usually analyzed to monitor the status of bearing. However, information on the status of bearing is always buried in heavy background noise; that is, status information of bearing is weaker than the background noise. Extracting the status features of bearing from signals buried in noise is difficult. Given this, a step-varying vibrational resonance (SVVR) method based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…One of the most important trends in development of chaos-based signal detection methods is communication where chaotic systems are used as highly sensitive input circuits of receivers [6]. Besides, high sensitivity of chaotic systems is used to diagnose mechanical faults [18] for the purpose of non-destructive testing. Application of a chaotic system to seismic signal processing was described in [19].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important trends in development of chaos-based signal detection methods is communication where chaotic systems are used as highly sensitive input circuits of receivers [6]. Besides, high sensitivity of chaotic systems is used to diagnose mechanical faults [18] for the purpose of non-destructive testing. Application of a chaotic system to seismic signal processing was described in [19].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…There is also an example of use of chaotic mapping in analysis of Internet traffic in order to detect LDoS attacks [20]. Studies [6,[18][19][20] also used a detection method using transition to the periodic state which is a significant drawback. Insufficient practical implementation of these methods is associated with the difficulty of maintaining a stable threshold of signal detection and the need to solve the problem of chaos identification.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia [26] proposed an improved SR method with an arbitrary stable-state potential for incipient bearing fault diagnosis. Liu [27] proposed a step-varying vibrational resonance (SVVR) method based on the duffing oscillator nonlinear system and concluded that the SVVR is more effective in extracting weak characteristic information than other methods. All in all, the second-order SR method is able to obtain higher output SNR and better performance than the first-order SR method.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practical engineering, the signal features are very weak and vulnerable to the influence of strong background noise [13,14], which is a typical nonstationary signal [15]. At this point, not all frequency bands in the signal have obvious fault characteristics.…”
Section: Introductionmentioning
confidence: 99%